Análise da eficiência energética das biomassas utilizadas em fornos cerâmicos na região de Tatuí-SP - Santos, Luis Ricardo Oliveira (2015)
Energy production in the form of heat from the burning of lignocellulosic materials is an interesting form of waste recovery. However, one needs to know the physical and chemical characteristics of a material before use it as biofuel. To obtain a ma terial application for energy purposes, it shall provide adequate moisture content, low ash content and high calorific value, all these combined with the availability of these residues in the market. Several factors hampering the use of lignocellulosic was tes as a main source of fuel as the lack of information on their characteristics, low density, high moisture content and ash content. This work aims to characterize physico - chemically different materials aiming its use for power generation. The materials u sed for this work were: Eucalyptus sp sawdust, sawdust of Pinus sp, sawdust Rubber sp... and sawdust Orange sp .. were conducted physico - chemical characterizations as: density (bulk and water displacement), immediate analysis (moisture content, ash content , volatile content and fixed carbon content), calorific value upper and lower energy density, chemical analysis of the materials (Klason lignin insoluble, holocellulose, a - cellulose and hemicellulose). The materials analyzed showed densities ranging from 1 74.46 to 246.26 Kg.m the Eucalyptus sp - 3 for Pinus sp. For the ash content materials showed variation from 0.76 to 1.60%, the Eucalyptus to provide the highest value, as well as the Rubber sp presented the highest value for the extractives, ranging from 8 - 21, 76%. Already the Orange sp had the highest Klason lignin content Insoluble of 39.24% which is high compared to other materials. The Eucalyptus sp was the material with the highest holocell ulose content 60.29% and 42.72% for a - cellulose content. The Rubber for hemicellulose content showed the highest value of 22.61%. For gross calorific value (PCS) all materials showed values in the range 4527 Kcal.Kg - 1a 4807 Kcal.Kg - 1. Pinus sp. was the mat erial that presented the highest value of 1183.77 cal / cm3 for energy density, followed by the rubber tree that showed the value of 1033.23 cal / cm3. Based on our results we can say that all four materials present in its composition features that allow t heir use as fuel. For this work we highlight the Pinus sp, because it was the material that presented values close to desirable for solid biofuels